2016
DOI: 10.1038/srep27663
|View full text |Cite
|
Sign up to set email alerts
|

The Use of NS1 Rapid Diagnostic Test and qRT-PCR to Complement IgM ELISA for Improved Dengue Diagnosis from Single Specimen

Abstract: Timely and accurate dengue diagnosis is important for differential diagnosis and immediate implementation of appropriate disease control measures. In this study, we compared the usefulness and applicability of NS1 RDT (NS1 Ag Strip) and qRT-PCR tests in complementing the IgM ELISA for dengue diagnosis on single serum specimen (n = 375). The NS1 Ag Strip and qRT-PCR showed a fair concordance (κ = 0.207, p = 0.001). While the NS1 Ag Strip showed higher positivity than qRT-PCR for acute (97.8% vs. 84.8%) and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 44 publications
4
35
0
1
Order By: Relevance
“…The serotype specific sensitivity and specificity showed that the RDT was less sensitive and specific in case of DENV‐3 in comparison to DENV‐1 and DENV‐2. Similar results are reported earlier …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The serotype specific sensitivity and specificity showed that the RDT was less sensitive and specific in case of DENV‐3 in comparison to DENV‐1 and DENV‐2. Similar results are reported earlier …”
Section: Discussionsupporting
confidence: 93%
“…These tests are economical and are easy to perform. Several studies have reported evaluation of RDTs, using different study designs and comparing the RDTs with ELISA, RT‐PCR, and qRT‐PCR in different conditions . But there are limited studies documenting DENV serotype specific evaluation of RDTs.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting viral Non Structural glycoprotein 1 (NS1) in the blood of patients represents an alternative path in the early diagnosis of flaviviruses. The assay can also be useful for epidemiological surveillance …”
Section: Introductionmentioning
confidence: 99%
“…The assay can also be useful for epidemiological surveillance. [5][6][7] NS1, a secreted viral glycoprotein produced by infected cells, is synthesized as a monomer and is dimerized rapidly after post-translational modifications in the endoplasmic reticulum. Dimers are transported to the cell surface and associate as hexamers that accumulate in large amounts in the extracellular medium.…”
Section: Introductionmentioning
confidence: 99%
“…In secondary DENV infection, however, a decreased sensitivity of the NS-1 Ag Strip test was observed. 43 The roles of DENV NS-1 antigen and lipid mediators such as (Platelet-Activating Factor) PAF in causing vascular leak are emerging DENV NS-1 are likely to be helpful in reducing disease pathogenesis due to NS-1, drugs that block PAF receptors or the pathways in which PAF is generated may be helpful in the treatment of acute illness. 20 PAF was previously found to be an important contributor to vascular leak and PAF receptor blockade was found to inhibit the effects of acute dengue sera on the expression of the tight junction protein ZO-1, and in the reduction of trans-endothelial resistance.…”
Section: Discussionmentioning
confidence: 99%